2018
DOI: 10.1590/s1414-40772018000300013
|View full text |Cite
|
Sign up to set email alerts
|

Perfil dos estudantes participantes do Programa Andifes de Mobilidade Acadêmica

Abstract: A mobilidade acadêmica constitui-se em um elemento importante para o ensino superior desde seus primórdios. Ao longo do processo de globalização, as políticas educacionais para internacionalização da educação foram intensificadas, ampliando a migração acadêmica temporária dos estudantes universitários. Na educação superior brasileira, constituída por um sistema complexo e diversificado de instituições públicas e privadas com diferentes tipos de cursos e programas, há as modalidades de mobilidade acadêmica inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…Regarding the self-reported race/skin color, most of the participants declared themselves white-skinned, as well as in a research study ( 19 ) which identified, over a period of 10 years, a mean enrollment of self-declared white-skinned students of 76.4%, while that of self-declared black-skinned students (black- and brown-skinned) corresponded to 21.7% (5.4% and 16.2%, respectively), evidencing that, although a growing entrance of the black Brazilian population in universities can already be observed, in some of them, this space continues to be mainly occupied by white-skinned individuals ( 21 - 22 ) .…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Regarding the self-reported race/skin color, most of the participants declared themselves white-skinned, as well as in a research study ( 19 ) which identified, over a period of 10 years, a mean enrollment of self-declared white-skinned students of 76.4%, while that of self-declared black-skinned students (black- and brown-skinned) corresponded to 21.7% (5.4% and 16.2%, respectively), evidencing that, although a growing entrance of the black Brazilian population in universities can already be observed, in some of them, this space continues to be mainly occupied by white-skinned individuals ( 21 - 22 ) .…”
Section: Discussionmentioning
confidence: 93%
“…evidencing that, although a growing entrance of the black Brazilian population in universities can already be observed, in some of them, this space continues to be mainly occupied by white-skinned individuals (21)(22) . drugs can trigger on the health of these young women (23)(24) .…”
Section: Discussionmentioning
confidence: 95%
“…From this perspective, the National Association of Rectors of Higher Education Federal Institutions (ANDIFES) launched in 2021 an academic mobility program called Promover, a platform that aims to provide VM for students of federal institutions. The program allowed students to take up to three different curricular components in up to three different federal institutions than the one in which they were regularly enrolled (Braz, 2015). With twelve universities in Promover's network, the first edition of the program offered 340 courses and 2,130 vacancies.…”
Section: Introductionmentioning
confidence: 99%